Professional development of teachers acting as bridges in online social networks - Maria Macià; Iolanda García (Association for Learning Technology, 2018)
Spanish K-12 teachers participate in online social networks to share educational resources and also to socialise with other teachers. In these networks, participants connected to several groups can adopt a bridging role. In general, 'bridging teachers' are more participative, engaged and they help to spread information through the network. In this study, we explore how bridging teachers use Twitter and whether this use results in a better outcome in their educational practices. Three kinds of data sources were analysed: teacher interviews, teachers' contributions on their own blogs and webpages, and teachers' Twitter activity. The analysis provided information on the participants' school practices, professional development, use of social networking sites and type of activity on Twitter. The results indicate that teachers acting as bridges use participatory methodologies combined with technology in their classroom and are active users of several social networking sites, although they prefer Twitter for professional matters. Regarding the use of Twitter, we have been able to identify two main patterns of interaction: one targeted at information sharing and the other focused on social relations.